Provenance and tectonic setting of the Lower Jurassic-Lower Cretaceous shales from the northeastern Iraq: mineralogical and geochemical approaches - Omar, Nagham; McCann, Tom; Al-Juboury, Ali I.; Al-Haj, Mohammed A.; Sharazwri, Arkan O.; Armstrong-Altrin, John S. (Frontiers in Earth Science, 2026)
The Lower Jurassic-Lower Cretaceous successions from the Ranya and Warte areas in the northeastern Iraq were investigated to determine the provenance and tectonic setting. Fifty-seven shale samples from six Jurassic-Lower Cretaceous formations, i.e., Sarki, Sehkaniyan, Sargelu, Naokelekan, Barsarin, and Chia Gara, were analyzed using X-ray diffraction (XRD), Scanning Electron Microscopy (SEM), and X-ray fluorescence (XRF). Mineralogical results showed that the shales comprise mainly calcite, dolomite and quartz, with traces of feldspar, illite/mica, kaolinite and chlorite. Geochemically, a range of elemental ratios, along with light rare earth elements heavy rare earth elements (HREE), revealed that felsic and intermediate igneous rocks constituted the predominant source rocks, whilst Eu/Eu* anomalies indicated a felsic provenance. The obtained mineralogical and geochemical data suggested that the sediments were derived from the igneous rocks in the Sanandaj–Sirjan Zone of Iran. Additionally, the tectonic discrimination diagrams revealed a passive margin setting, which is consistent with the tectonic province of the Ranya and Warte shale successions of northeastern Iraq.